MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MUATAN MATEMATIKA KELAS IV MENGGUNAKAN MODEL INGAT DI SEKOLAH DASAR - Diah Fitriani; Fathul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to overcome the low critical thinking skills of students in learning Mathematics. The problem is caused by the lack of active involvement of students in the learning process. The solution applied is the use of the INGAT model, a combination of PBL, TGT, and Snowball Throwing models. This research used the Classroom Action Research (PTK) method for four meetings, with the subject of 20 fourth grade students of SDN Alalak Selatan 2 Banjarmasin. Through Classroom Action Research in class IV, the results showed that critical thinking skills and learning outcomes of students have increased significantly. The INGAT learning model is proven to be effective in increasing learner engagement and learning outcomes. This research can be used as a reference or alternative in improving the quality of mathematics learning in elementary schools.